Evaluasi sistem pengendalian intern penatausahaan barang milik negara pada kantor badan pengawasan keuangan dan pembangunan perwakilan provinsi sulawesi utara - Pulakiang, Judhystira Viyanthy; Ilat, Ventje; Wokas, Heince R.N (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2021)
The purpose of this study is to determine the implementation of the Internal Control System for the Administration of State Property at the BPKP Representative Office of North Sulawesi Province. This research was carried out at the Financial and Development Supervisory Agency for North Sulawesi Province, the time was carried out from April 2021 to July 2021. The analytical method used to discuss the problems in this study was descriptive analysis method. The data collection method used in this research is primary data such as interviews and documentation. The results showed that the Internal Control System for the Administration of State Property at the BPKP Representative Office of North Sulawesi Province had been carried out well. For this reason, the agency is expected to be able to maximize every element of internal control in the administration of state property.